FINANCIAL INCLUSION DAN PEMBIAYAAN PERBANKAN SYARIAH DALAM MEMPENGARUHI PERKEMBANGAN UMKM SERTA DAMPAKNYA PADA PERTUMBUHAN EKONOMI INDONESIA - Fitriyanto, Doni (Commodities, Journal of Economic and Business, 2021)
The research in this thesis is motivated by the difficulty of accessing capital that reaches the MSMEs layer, which is not in line with the concept of financial inclusion that is being promoted by the Government. Financial inclusion is promoted to answer these problems through deepening financial access, with Islamic banking financing to the public, especially MSMEs. So that the realization of better distribution and economic growth in Indonesia. The research method in this thesis uses a quantitative approach, with the type of research being explanatory research. The total number of samples is 132 research samples. The data analysis of this research uses Structural Equation Modeling (SEM). with the help of the SmartPLS 3.2.8 program. The results of the study show that: (1) Financial Inclusion has a positive effect on the development of MSMEs in Indonesia. (2) Islamic Banking Financing has a positive and significant impact on the development of MSMEs in Indonesia. (3) Financial Inclusion has a positive effect on economic growth in Indonesia. (4) Islamic Banking Financing has a positive and significant impact on Indonesia's economic growth. And (5) The development of MSMEs has a positive and significant impact on Indonesia's economic growth.